F‐box protein FBXL2 inhibits gastric cancer proliferation by ubiquitin‐mediated degradation of forkhead box M1. Issue 4 (8th February 2016) - Li, Liang‐qing; Pan, Dun; Chen, Hui; Zhang, Lin; Xie, Wen‐jun
Abstract : F‐box/LRR‐repeat protein 2 (FBXL2), a component of Skp‐Cullin‐F box (SCF) ubiquitin E3 ligase, has been shown to inhibit tumorigenesis by targeting and ubiquitinating several oncoproteins. However, its role in gastric cancer remains poorly understood. Here, by tandem mass spectrometry, we show that FBXL2 interacts with forkhead box M1 (FoxM1) transcription factor. As a result, FBXL2 promotes ubiquitination and degradation of FoxM1 in gastric cancer cells. Furthermore, overexpression of FBXL2 inhibits, while its deficiency promotes cell proliferation and invasion. Expression levels of cell‐cycle regulators (Cdc25B and p27), which are down‐stream target effectors of FoxM1, are also regulated by FBXL2. Therefore, our results uncover a previous unknown network involving FBXL2 and FoxM1 in the regulation of gastric cancer growth. Abstract :